Comparison of Efficacy of Combination Therapy (Tamsulosin + Solifenacin) Versus Monotherapy (Tamsulosin) Alone for Double J Stent Related Lower Urinary Tract Symptoms - Javaid, Waleed; Akmal, Muhammad; Sohail, Zaighum; Dastgir, Munzir Bin; Irshad, Rana Farrukh (Indus Journal of Bioscience Research, 2025)
Objectives: To compare the efficacy of combination therapy (Tamsulosin + Solifenacin) versus monotherapy (Tamsulosin) in relieving DJ stent-related LUTS. Methodology: The study was conducted at Department of Urology, Allied Hospital, Faisalabad from 31 January 2025 to 30 April 2025. Sixty patients aged between 18 and 40 years who underwent unilateral DJ stent placement were selected through non-probability consecutive sampling and randomly divided into two groups: Group A received combination therapy, while Group B received monotherapy. The International Prostate Symptom Score (IPSS) questionnaire was administered at baseline and at four weeks following surgery to assess LUTS severity. Results: Patients in the combination group showed a significantly greater reduction in mean IPSS scores (from 9.55 ± 1.94 to 4.79 ± 1.92) compared to the monotherapy group (from 10.95 ± 2.17 to 6.33 ± 1.64), with a post-treatment p-value of 0.001. Conclusion: Combination therapy with Tamsulosin and Solifenacin is significantly more effective than Tamsulosin alone in managing DJ stent-related LUTS. These findings support the routine use of dual pharmacotherapy to improve symptom relief and patient comfort during stent indwelling.